Online Single Submission Risk Based Approach: Conflict of Authority Between Central and Local Government - M. Angga Maulana Hasibuan (Locus Journal of Academic Literature Review, 2022)
After the enactment of Law 11 of 2020 on Job Creation all licenses are only through one portal, namely through the Online Single Submission Risk, meaning that the regulation also implements an effort in the process of simplifying business licensing from initially license-based (license approach) to risk-based and business scale (risk-based approach). Therefore, the purpose of this study is to analyze the licensing simplification strategy through legal instruments, analyze and explain whether or not there is a conflict of interest between the central and regional governments regarding the authority to implement the risk-based online single submission system licensing. The type of research used in is normative juridical legal research. The nature of this research is descriptive. The approaches used in this research are statute approach, comparative approach. The data used consists of secondary data collected using library research techniques. Furthermore, all data were analyzed using qualitative data analysis methods. Based on the results of the research, the implementation of Risk-Based Online Single Submission licensing still has the uncertainty of the regulations governing it. The conflict in question is the scope of the aspects of responsibility and liability that are directly correlated with the relative competence or scope of authority of the place of trial in the state administrative court related to licensing cases as one aspect of the exercise of authority in government administration. Where it is the result of unclear authority arrangements as described in the Government Ordinance on the Risk-Based Online Single Submission system. The need for the Government to strengthen, reinforce, and reorganize the authority related to licensing through risk-based Online Single Submission, and the Government needs to put aside the sectoral ego of each inter-agency related to licensing implementation. This is done in order to realize the essence of "Single Submission" in the business licensing.